Gambaran Pengetahuan Ibu Hamil Tentang Perawatan Tali Pusat Pada Bayi Baru Lahir Di Klinik Pratama Tanjung Delitua Tahun 2024 - -, Ruseni; -, Masni (Universitas Prima Indonesia, 2024)
According to the World Health Organization (WHO) in 2019, neonatal deaths caused by neonatal tetanus in Southeast Asian countries totaled 581 babies, while neonatal tetanus cases in Indonesia in 2019 were reported at 84 babies from 15 provinces, with an increase of 54 cases attributed to risk factors related to umbilical cord care. This study aims to explore the knowledge of pregnant women regarding umbilical cord care for newborns at Pratama Tanjung Delitua Clinic in 2024. The research is descriptive in nature, using primary data obtained directly from respondents. The population in this study consists of all pregnant women at the Pratama Tanjung Delitua Clinic, totaling 20 respondents, with the sample selected using accidental sampling. Data analysis is presented in the form of frequency distribution tables, supported by existing theories and references. The majority of respondents (10 respondents or 50%) were found to have poor knowledge, while a minority (2 respondents or 10%) had sufficient knowledge. Based on age characteristics, the majority with poor knowledge were aged 20–35 years, accounting for 5 respondents (25%). Based on educational background, the majority with poor knowledge had only completed elementary school, totaling 4 respondents (20%). Based on occupation, the majority with poor knowledge were housewives (IRT), amounting to 8 respondents (40%). Based on parity, the majority with poor knowledge were primiparous (first-time mothers), totaling 7 respondents (35%). Lastly, based on information sources, the majority with poor knowledge cited parents and friends as their sources, totaling 9 respondents (45%). It can be concluded that the respondents have insufficient knowledge regarding umbilical cord care for newborns. Therefore, it is recommended that pregnant women improve their knowledge about the importance of umbilical cord care for newborns through better information sources.